Welfare reform in rural places comparative perspectives - Milbourne, Paul, 1966-; Marsden, Terry (Research in rural sociology and development ;, 2010)
Research on welfare has tended to focus on the national scale with relatively little attention given to the differential impacts of welfare restructuring in rural places and the difficulties faced by disadvantaged groups with limited provision of welfare services in many rural areas. This book seeks to significantly extend previous research work on the rural impacts of national welfare reform and position it in a broader context. "International Perspectives on Rural Welfare" provides a critical, comprehensive and comparative account of the rural dimensions of welfare in a number of developed countries. The book brings together recent research from Europe, North America, Australia and New Zealand to provide the seminal international book on rural welfare. As well as being international in its outlook, it provides an inter-disciplinary focus on rural welfare by including contributors from sociology, human geography, social policy and social anthropology. The definition of welfare used within the book is broad, encompassing overarching welfare and workfare agendas, as well as more specific welfare policy areas such as anti-poverty, health, housing, social security, social work and education.